How can the African Continental Free Trade Area (AfCFTA) help develop regional value chains across Africa? An Exploration - (:unkn) unknown (My University, 2024)
All African countries participate in the African Continental Free Trade Area (AfCFTA) to boost intra-African trade to accelerate structural transformation. At the same time, increasing geopolitical tensions around the world are pressuring countries to ‘reshore’ by retreating from engagement in Global Value Chains (GVCs) towards Regional Value Chains (RVCs). High values for RVC indices would indicate that African exports have a high import content of intermediates originating in Africa and that exports destined to other African countries undergo further processing, an indication of structural transformation. The paper uses the EORA Multi-regional Input-Output (MRIO) data over 1995-2022 to present new, more comprehensive measures of participation in supply chains at several levels: across countries, regions, and sectors. Comparisons are with countries (e.g. China or India) and aggregates of countries (e.g. Europe, Americas, Asia) engaged in deep market integration. Measures for 50 African countries are compared with those for other regions.
Keywords: African Research